Multiple criteria approach in the mining method selection - Popovic, Gabrijela; Djordjevic, Bojan; Milanovic, Dragan (Industrija, 2019)
Underground mining method selection is a very complex task for the mining engineers because the chosen method should fulfill the technical, economic and production requirements. Combining the criteria that cover different aspects of the mining operation and group decision-making increases the reliability of the decisions and minimize its subjectivity.  The main objective of this paper is to propose the methodology for the underground mining method selection based on the Extended Pivot Pairwise Relative Criteria Importance Assessment (PIPRECIA-E) and group decision-making. The applicability of the proposed methodology is demonstrated by using the numerical example inclusive of 3 main criteria, 18 sub-criteria and 5 alternative underground mining methods pointed to the exploitation of the Upper Zone of the Čukaru Peki deposit in Serbia.
Keywords: Group Decision Making; Čukaru Peki; underground mining method selection; PIPRECIA-E; Multiple-Criteria Decision-Making